Consensus guidelines on severe acute pancreatitis. Issue 7 (July 2015) - The Italian Association for the Study of the Pancreas (AISP); Pezzilli, Raffaele; Zerbi, Alessandro; Campra, Donata; Capurso, Gabriele; Golfieri, Rita; Arcidiacono, Paolo G.; Billi, Paola; Butturini, Giovanni; Calculli, Lucia; Cannizzaro, Renato; Carrara, Silvia; et al.
Abstract This Position Paper contains clinically oriented guidelines by the Italian Association for the Study of the Pancreas (AISP) for the diagnosis and treatment of severe acute pancreatitis. The statements were formulated by three working groups of experts who searched and analysed the most recent literature; a consensus process was then performed using a modified Delphi procedure. The statements provide recommendations on the most appropriate definition of the complications of severe acute pancreatitis, the diagnostic approach and the timing of conservative as well as interventional endoscopic, radiological and surgical treatments.